The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1021/jacs.2c12517
|View full text |Cite
|
Sign up to set email alerts
|

Embedding Peptides into Synthetic Polymers: Radical Ring-Opening Copolymerization of Cyclic Peptides

Abstract: Biopolymers such as proteins and nucleic acids are the key building blocks of life. Synthetic polymers have nevertheless revolutionized our everyday life through their robust synthetic accessibility. Combining the unmatched functionality of biopolymers with the robustness of tailorable synthetic polymers holds the promise to create materials that can be designed ad hoc for a wide array of applications. Radical polymerization is the most widely applied polymerization technique in both fundamental science and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Recently, various research groups have reported the statistical copolymerization of cyclic monomers with vinyl monomers to produce hydrolytically degradable copolymer backbones [19,20,21,22,26,29–31,34,37,38] . In principle, this approach could form part of the solution to the global challenge of plastic waste [39,40] .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, various research groups have reported the statistical copolymerization of cyclic monomers with vinyl monomers to produce hydrolytically degradable copolymer backbones [19,20,21,22,26,29–31,34,37,38] . In principle, this approach could form part of the solution to the global challenge of plastic waste [39,40] .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, various research groups have reported the statistical copolymerization of cyclic monomers with vinyl monomers to produce hydrolytically degradable copolymer backbones [19,20,21,22,26,29–31,34,37,38] . In principle, this approach could form part of the solution to the global challenge of plastic waste [39,40] .…”
Section: Resultsmentioning
confidence: 99%
“…In theory, the controlled ROP of macrocyclic monomers can be achieved by combining rapid and simultaneous initiation reactions. To date, controlled ring-opening metathesis polymerization (ROMP) and controlled radical ROP of macrocyclic monomers with living polymerization characteristics have been developed based on this strategy and applied in the synthesis of polymers with controlled molecular weights and relatively narrow dispersities ( Đ ≤ 1.4). Specifically, sequence-controlled polymers have been synthesized by controlled ROMP using a 1,6-enyne metathesis cascade motif, , cis -olefin, or a strained 3-substituted cyclooctene as the ring-opening trigger.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, sequence-controlled polymers have been synthesized by controlled ROMP using a 1,6-enyne metathesis cascade motif, , cis -olefin, or a strained 3-substituted cyclooctene as the ring-opening trigger. Backbone-functionalized polymers have been synthesized from macrocycles containing an allylic sulfone radical cascade moiety by controlled radical ROP assisted with reversible addition–fragmentation chain transfer polymerization technique. Although these metathesis and radical cascade reactions facilitate controlled ROP of macrocyclic monomers, the trigger moieties used are all incorporated into the resultant polymer chains. , This inevitably produces unnecessary bulky auxiliary groups on the backbones of the obtained polymers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation